Pengaruh Layanan Google Terhadap Motivasi Belajar Untuk Mendukung Prestasi Belajar Siswa - Muhammad Haviz Irfani; Daniel Udjulawa (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2017)
Information technology in education sector affected on learning process held by senior high school in Palembang city. Some 77,43% computer users (including students) who visit the google pages with the number of of 4,464,000,000 visitors everyday. Particularly students are very depend on search engine to to search of information or matter to complete a task school that relies heavily with the internet, thereby should be tested what factors affecting and could provide motivation to study and improve student learning achievements. The results of literature give you some of factors affect the motivation to study and student learning achievements that is a source of learning, intensity using, the quality of information. The methodology used namely AMOS (Analysis of Moment Structure), and path analysis, calculation the probability between endogenous, or endogenous and exogenous by the application of SEM (Structural Equation Model). The results of the study gained may be used as input for school management to make maximum use of google search engine in increased the motivation to study and student learning achievements